2015
DOI: 10.5194/gmd-8-3349-2015
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the WRF model to PBL parametrisations and nesting techniques: evaluation of wind storms over complex terrain

Abstract: Abstract. Simulating surface wind over complex terrain is a challenge in regional climate modelling. Therefore, this study aims at identifying a set-up of the Weather Research and Forecasting Model (WRF) model that minimises systematic errors of surface winds in hindcast simulations. Major factors of the model configuration are tested to find a suitable set-up: the horizontal resolution, the planetary boundary layer (PBL) parameterisation scheme and the way the WRF is nested to the driving data set. Hence, a n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 55 publications
5
45
0
Order By: Relevance
“…This hypothesis is also verified by the ME analysis of the simulated geopotential height at different levels (data not shown). Furthermore, a very consistent result was the overestimation of wind in the CTL, and was in good agreement with previous studies [20,33,44], which believed that it was partly due to the poor representation of the unresolved topography. Gómez-Navarro et al [20] pointed out that the bias could be reduced effectively by a change of PBL scheme, the use of nudging, and improvement of horizontal resolution.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This hypothesis is also verified by the ME analysis of the simulated geopotential height at different levels (data not shown). Furthermore, a very consistent result was the overestimation of wind in the CTL, and was in good agreement with previous studies [20,33,44], which believed that it was partly due to the poor representation of the unresolved topography. Gómez-Navarro et al [20] pointed out that the bias could be reduced effectively by a change of PBL scheme, the use of nudging, and improvement of horizontal resolution.…”
Section: Discussionsupporting
confidence: 79%
“…Recently, research on the nudging application and comparison of two nudging schemes (grid nudging and spectral nudging) has been very common [17][18][19][20][21][22][23]; however, a consistent conclusion is still lacking. Logically, spectral nudging is superior to grid nudging [24], but many findings [17,22,23] have shown that, in some cases, grid nudging is better than spectral nudging.…”
Section: Introductionmentioning
confidence: 99%
“…). A standard resolution for present‐day and future RCMs is 10–25 km, and is increased to 1–3 km for specific applications . For paleoclimate applications, the spatial resolution has usually been limited to about 50 km due to the demand of longer simulation periods, requiring a high amount of computational resources.…”
Section: Models and Boundary Conditionsmentioning
confidence: 99%
“…The choice of groupings was based mainly on two criteria: (1) it was possible to form groups with at least six members in each group and (2) each of the options was highlighted in the literature as being important for model performance (Hahmann et al, 2015b;Gómez-Navarro et al, 2015;Carvalho et al, 2012;Draxl et al, 2014). Several other setup options were considered: MM, LSM, land cover, spin-up time, and data set used for initial and boundary conditions, but either it was not possible to group them in a meaningful way, or they were deemed of too little importance based on previous studies.…”
Section: Relating Performance To Model Setupmentioning
confidence: 99%
“…They showed that the Pleim-Xiu SL scheme (Pleim, 2006) combined with the ACM2 PBL scheme (Pleim, 2007b) gave the smallest errors for wind speed and wind energy production estimates across the sites, while the quasi-normal scale elimination (QNSE) SL and PBL schemes (Sukoriansky et al, 2005) gave smaller errors for offshore sites. In a similar study, Gómez-Navarro et al (2015) analyzed the sensitivities of the WRF model to the choice of PBL scheme and grid spacing in complex terrain in Switzerland. They found that using a modified version of the YSU PBL scheme, which accounts for effects of unresolved topography (Jiménez and Dudhia, 2012), in combination with the smallest grid spacing (2 km) and analysis nudging gave the best agreements with measurements during a number of wind storms.…”
Section: Introductionmentioning
confidence: 99%